Maternal and Perinatal Complications in Pre-eclampsia - Acharya, Sarita; Pal, M N (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Hypertensive disorders of pregnancy is one of the major causes of maternal morbidity/mortality- leading to 10-15% of maternal deaths in low - and middle-income countries. Pre-eclampsia produces potentially lethal complications including abruptio placenta, disseminated intravascular coagulation, intracranial hemorrhage, hepatic failure, acute renal failure, and cardiovascular collapse. Intrauterine fetal growth restriction, intrauterine fetal demise and prematurity are the other related obstetric problems. The current study aimed to find the maternal and perinatal complications of pre- eclampsia in our context. MATERIAL AND METHODS: A prospective study of 145 patients with the diagnosis of pre-eclampsia treated in a tertiary level teaching hospital between June 2011 to December 2013 was done. Hypertension in pregnancy, pre-eclampsia, severe pre-eclampsia and eclampsia were defined in the standard way. Maternal and perinatal complications were identified and analyzed. RESULTS: Pre-eclampsia was detected in 6.02% of all deliveries. Maternal complications were abruptio placenta (11.03%), eclampsia (8.27 %), HELLP syndrome (4.12%), hypertensive encephalopathy (0.7%), acute renal failure (0.7%) and maternal death (0.7%). Fetal complications included preterm delivery (17.93%), intra uterine growth restriction (10.34%), intra uterine death (8.30%) and neonatal death(2.80%). CONCLUSION: Pre-eclampsia is associated with increased maternal-perinatal complications. The adverse outcome can be minimized by more widespread use of prenatal care, education of primary medical care personnel, prompt diagnosis of high-risk patients and timely referral to tertiary medical centers. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 21-25